(untitled) (Journal of Pathology of Nepal, 2016)
Prostatic intraepithelial neoplasia is preneoplastic lesion described from early of this 20th century. PIN includes a spectrum of features ranging from low grade to high grade neoplasia. The studies are focused on their influence to predict the occurence of prostatic carcinoma. This review analyses the various development in the identification and differentiation of PIN and their clinical implication.